2017
DOI: 10.1167/17.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of retinal image motion at the limits of spatial vision

Abstract: Even during fixation, our eyes are constantly in motion, creating an ever-changing signal in each photoreceptor. Neuronal processes can exploit such transient signals to serve spatial vision, but it is not known how our finest visual acuity—one that we use for deciphering small letters or identifying distant faces and objects—is maintained when confronted with such change. We used an adaptive optics scanning laser ophthalmoscope to precisely control the spatiotemporal input on a photoreceptor scale in human ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 45 publications
7
90
2
Order By: Relevance
“…Interestingly, both WTs and Dcdc2 KOs displayed better performance when motion was added to the stimuli, however, Dcdc2 KOs consistently scored lower on percent correct compared with WTs (Figure B,C). This parallels with human findings showing that when motion is added to stimuli acuities were approximately 25% better compared with stimuli without motion . After weeks of moving Gabor testing, subjects advanced to the most difficult task, moving dots.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, both WTs and Dcdc2 KOs displayed better performance when motion was added to the stimuli, however, Dcdc2 KOs consistently scored lower on percent correct compared with WTs (Figure B,C). This parallels with human findings showing that when motion is added to stimuli acuities were approximately 25% better compared with stimuli without motion . After weeks of moving Gabor testing, subjects advanced to the most difficult task, moving dots.…”
Section: Discussionsupporting
confidence: 83%
“…This parallels with human findings showing that when motion is added to stimuli acuities were approximately 25% better compared with stimuli without motion. 83 After weeks of moving Gabor testing, subjects advanced to the most difficult task, moving dots. Here, Dcdc2 KOs showed percent correct means that hovered at chance levels while WTs consistently scored above chance after the first week of testing resulting in a significant Genotype effect ( Figure 2D).…”
Section: Discussionmentioning
confidence: 99%
“…Our results might seem inconsistent with previous reports where complete retinal stabilization resulted in impaired discrimination performance (Ratnam et al, 2017; Rucci et al, 2007). A simple interpolation between the two extremes suggests a monotonic impairment in visual performance with better compensation for FEM.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous research showed that naturally occurring or artificially induced irregular and continuous retinal image drifts help in seeing fine spatial details (Ratnam, Harmening, & Roorda, 2017; Rucci et al, 2007). Likewise, naturally occurring microsaccades or sudden jumps of stimuli are known to counteract visual fading (Costela, McCamy, Macknik, Otero-Millan, & Martinez-Conde, 2013; Martinez-Conde, Otero-Millan, & Macknik, 2013!…”
Section: Introductionmentioning
confidence: 99%
“…However, visual acuity and contrast sensitivity to high-frequency interference fringes-tasks reliant on mechanisms with even finer neural sampling-are generally unaffected when probed with a moving stimulus (Packer & Williams, 1992;Westheimer & McKee, 1975). Moreover, it has been suggested that the visual system may harness the spatiotemporal fluctuations in cone signals produced by eye movements to improve the detection of fine-grained targets (Kuang, Poletti, Victor, & Rucci, 2012;Ratnam, Domdei, Harmening, & Roorda, 2017;Rucci, Iovin, Poletti, & Santini, 2007;Rucci & Victor, 2015). The present findings are consistent with the view that the visual system is equipped with mechanisms capable of disregarding-and in some cases capitalizing on-the retinal image blur introduced by the unsteady eye.…”
Section: Discussionmentioning
confidence: 99%